2022
DOI: 10.1021/acsami.2c17358
|View full text |Cite
|
Sign up to set email alerts
|

Design of Monovalent Cerium-Based Metal Organic Frameworks as Bioinspired Superoxide Dismutase Mimics for Ionizing Radiation Protection

Abstract: Superoxide dismutase (SOD) is one of the major antioxidants in vivo and is expected to play critical roles on the defense against reactive oxygen species (ROS)-mediated damages, such as ionizing radiation damages. Herein, inspired by the function and structure of natural SODs and cerium oxide nanozymes, two monovalent cerium-based metal organic frameworks (Ce-MOFs), CeIIIBTC and CeIVBTC, were designed for superoxide radical (O2 •–) elimination and ionizing radiation protection. These two Ce-MOFs selectively sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…34−37 We first chose Ce-MOF-808 NPs as our study model, which were fabricated as reported. 38 As shown in Figure 1c, the experimental Ce-MOF-808 NPs exhibited an irregular morphology. The X-ray diffraction (XRD) pattern of the experimental Ce-MOF-808 NPs corresponded well to the simulated MOF-808, which indicated the successful synthesis of Ce-MOF-808 NPs (Figure 1d).…”
Section: ■ Results and Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…34−37 We first chose Ce-MOF-808 NPs as our study model, which were fabricated as reported. 38 As shown in Figure 1c, the experimental Ce-MOF-808 NPs exhibited an irregular morphology. The X-ray diffraction (XRD) pattern of the experimental Ce-MOF-808 NPs corresponded well to the simulated MOF-808, which indicated the successful synthesis of Ce-MOF-808 NPs (Figure 1d).…”
Section: ■ Results and Discussionmentioning
confidence: 82%
“…As expected, the activity of alkaline phosphatase decreased with increasing concentrations of added HPO 4 2– (Figure S1). Ce 6 cluster-based MOF (Ce-MOF) NPs are well known for their alkaline phosphatase-mimicking activities, and Ce 6 clusters serve as catalytic active centers. We first chose Ce-MOF-808 NPs as our study model, which were fabricated as reported . As shown in Figure c, the experimental Ce-MOF-808 NPs exhibited an irregular morphology.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ce-MOFs Superoxide dismutase CHO cells [54] PB@MSCM Oxidase Hematopoietic cells [55] F I G U R E 1 Schematic illustration of enzyodynamic therapy (EDT) at nanoscale for representative nanozyme paradigms, advantages of EDT and versatile biomedical applications, including ROS-producing EDT and ROS-scavenging EDT. Created by BioRender.…”
Section: Superoxide Dismutasementioning
confidence: 99%
“…One of the main mechanisms of radiation damage effect is the free radical damage, because the radiation decomposition of biological molecules is the main chemical pathway to produce free radicals. 54 Free radicals not only play an important role in the process of acute radiation disease, but also continue to cause tissue damage during the acute phase following the latent phase. Research shows that the free radicals produced by radiation, especially ROS, are one of the main causes of damage.…”
Section: Protection Of Radiation-induced Ros Damagementioning
confidence: 99%